Randomized Study of Long-term (15-17 Years) Outcome After Microfracture Versus Mosaicplasty in Knee Articular Cartilage Defects - Solheim, Eirik; Hegna, Janne; Strand, Torbjørn; Harlem, Thomas; Inderhaug, Eivind (The American journal of sports medicine, 2018)
Few comparative randomized long-term studies on microfracture versus mosaicplasty have been published, and only 2 studies reported a follow-up of 10 years. Hypothesis/Purpose: The purpose was to compare the clinical outcome of microfracture versus mosaicplasty/osteochondral autograft transfer in symptomatic cartilage lesions. The null hypothesis was that the outcome was not statistically different at any point of time. Randomized controlled trial; Level of evidence, 1. Forty patients with articular cartilage defects were randomized to undergo cartilage repair by either microfracture (n = 20) or mosaicplasty (n = 20). Inclusion criteria were as follows: age 18 to 50 years at the time of surgery, 1 or 2 symptomatic focal full-thickness articular chondral defects on the femoral condyles or trochlea, and size 2 to 6 cm . The main outcome variable was the Lysholm knee score recorded before the surgery and at 12 months, median 5 years, median 10 years, and minimum 15 years after the surgery. Forty patients were included in the study (28 men, 12 women; median age, 32 years; range, 18-48 years). Defects with a median size of 3.5 cm (range, 2-5 cm ) were treated. A significant increase in the Lysholm score was seen for all subjects- from a mean 53 (SD, 16) at baseline to 69 (SD, 21) at the minimum 15-year follow-up ( P = .001). The mean Lysholm score was significantly higher in the mosaicplasty group than the microfracture group at 12 months, median 5 years, median 10 years, and minimum 15 years: 77 (SD, 17) versus 61 (SD, 22), respectively ( P = .01), at the last follow-up. At all follow-up time points, the difference in mean Lysholm score was clinically significant (>10 points). At short, medium, and long term (minimum 15 years), mosaicplasty results in a better, clinically relevant outcome than microfracture in articular cartilage defects (2-5 cm ) of the distal femur of the knee in patients aged 18 to 50 years.